Microband-Induced Plasticity in a Nb Content Fe–28Mn–10Al–C Low Density Steel - Tao Ma; Jianxin Gao; Huirong Li; Changqing Li; Haichao Zhang; Yungang Li (Metals, 2021)
Novel Fe–28Mn–10Al–C–0.5Nb low-density steel was developed and the room temperature tensile behavior in the solid solution state and the microstructure evolution process during plastic deformation were studied, aiming to clarify the dominant deformation mechanisms. The results show that the developed steel was fully austenitic with a low density of 6.63 g/cm3 and fairly high stacking fault energy of 84 MJ/m2. The present fully austenitic Fe–28Mn–10Al–C–0.5Nb low-density steel exhibited an excellent ultimate tensile strength of 1084 MPa and elongation of 37.5%; in addition, the steel exhibited an excellent combination of strength and ductility (i.e., the product of strength and ductility (PSE) could reach as high as 40.65 GPa%). In spite of the high stacking fault energy, deformed microstructures exhibited planar glide characteristics, seemingly due to the glide plane softening effect. The excellent combination of strength and ductility is attributed to plasticity induced by microbands and leads to the continuous strain hardening during deformation at room temperature. Moreover, the addition of Nb does not change the deformation mechanism and strengthening mechanism of Fe–Mn–Al–C low-density steel, and can optimize the mechanical properties of the steel.